PENINGKATAN KEMANDIRIAN ANAK USIA DINI MELALUI MEDIA BIG BOOK ANAK KELOMPOK B TK PUTRA PERTIWI XXI SUMBERARUM - Surti Surti; Octavian Dwitanto; wening sekar kusuma (Jurnal Kajian Anak (J-Sanak), 2023)
This study aims to increase children's independence and to determine children's independence in Group B TK Putra Pertiwi XXI Sumberarum after applying the big book media. The subjects of this study were the children of group B TK Putra Pertiwi XXI Sumberarum. This study uses Classroom Action Research (PTK) which is carried out in two cycles in each activity, with each activity per cycle consisting of planning, implementing, observing, and reflecting. The use of big book media adapted to existing themes as a source of learning is proven to be able to increase the independence of group B children in Putra Pertiwi XXI Sumberarum Kindergarten. The results in cycle I obtained a percentage of 70% and the increase in child independence in cycle II obtained results of 90%, with these results indicating that this research was successful or increased because it exceeded the research indicator targets that had been set, which was 80%. Big book media as a learning medium can be said to be successful in increasing children's independence if in this learning children are able to be independent in doing things on their own without the help of others.